On The Fate of Intellectuals Exiled To the Central Asian Labor Camp - Yuldasheva, Nilufar Nazarovna (RA Journal of Applied Research, 2022)
The inhuman policy pursued by the Soviet authorities in the 1930s throughout the Soviet Union, known as the "Great Terror" and the "Red Terror", resulted in the tragic death of millions of innocent people. The main goal of the Soviets was to use their intelligence and labor to imprison dissidents, intellectuals living in different regions of the USSR, by force and unjust accusations. Prisoners were mainly involved in heavy labor-intensive work, such as large-scale construction, canal digging, construction of hydroelectric power stations, work in factories, and working in state and collective farm fields.